Representations of real and p-adic groups - Tan, Eng-chye; Zhu, Chen-bo (Lecture notes series (National University of Singapore. Institute for Mathematical Sciences), 2004)
This invaluable volume collects the expanded lecture notes of thosetutorials. The topics covered include uncertainty principles forlocally compact abelian groups, fundamentals of representations ofp-adic groups, the Harish?Chandra?Howe local characterexpansion, classification of the square-integrable representationsmodulo cuspidal data, Dirac cohomology and Vogan's conjecture, multiplicity-free actions and Schur?Weyl?Howe duality.